2019
DOI: 10.21873/invivo.11767
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events of Concurrent Radiotherapy and ALK Inhibitors for Brain Metastases of ALK-Rearranged Lung Adenocarcinoma

Abstract: Background: We investigated acute adverse events in patients with brain metastases (BMs) of anaplastic lymphoma kinase-rearranged (ALKr) non-small cell lung cancer (NSCLC) treated with both cranial radiotherapy and tyrosine kinase inhibitors (TKIs) of ALK. Patients and Methods: Acute AEs were retrospectively investigated in patients with BMs of ALKr-NSCLC who received both wholebrain radiotherapy (WBRT) and ALK-TKI. For comparison, they were also assessed in patients with epidermal growth factor receptor (EGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In a meta-analysis, Singh et al reported no significant difference in efficacy between combined radiotherapy and TKI therapy and radiotherapy alone. Similarly, there was no significant difference in median overall survival between the TKI, radiotherapy, and combination alternatives (23). Thus, treatment should be selected according to the specific situation of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…In a meta-analysis, Singh et al reported no significant difference in efficacy between combined radiotherapy and TKI therapy and radiotherapy alone. Similarly, there was no significant difference in median overall survival between the TKI, radiotherapy, and combination alternatives (23). Thus, treatment should be selected according to the specific situation of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…The AE produced by combination therapy cannot be ignored. Different from the previous sequential administration, a Japanese team administered ALK-TKI (Crizotinib/Alectinib/Ceritinib) and WBRT simultaneously to patients with brain metastasis of ALK rearranged NSCLC for the first time, and found that this method may cause serious ototoxicity ( 43 ).…”
Section: Alk/ros1-tki Combined With Radiotherapymentioning
confidence: 99%
“…For ALK TKIs, there is currently minimal evidence for or against their combined use with irradiation; one retrospective study of ALKr NSCLC patients suggested an increase in ototoxicity with combined ALK TKIs and WBRT (87). For WBRT (where the globes receive radiation dose), care may need to be exerted because of potential overlapping ocular toxicity with crizotinib (83).…”
Section: Combination Of Targeted Therapies and Icis With Srsmentioning
confidence: 99%